Islamic pedagogics educational implementation based on Quran and Sunnah at Darul Hikam High School - Bawadi, Titik Handayani; Prasetio, Bayu; Silalahi, Binsar; Sapardi, Endang (LPPM Universitas Ibn Khaldun, Bogor, 2024)
Islamic Pedagogics is a science that studies how to educate and guide children (students) based on Islamic values derived from the Quran and Sunnah. The main principle of Islamic Pedagogics is Tauhid (Oneness with Allah), which is realized through education that prioritizes Adab and Science to form individuals with noble characters. The Research in this scientific article aims to explore and analyze the implementation of Islamic Pedagogics in student character building at Darul Hikam High School. This study uses a qualitative approach, employing literature study and observation methods conducted at Darul Hikam High School. The results show that Darul Hikam High School, as an Islamic institution, has adopted Islamic Pedagogics in every aspect of education. However, to implement Islamic Pedagogics effectively, schools must continually evaluate and improve teachers' competencies, particularly in Islamic Pedagogy. Therefore, routine and periodic coaching for every teacher and educator is necessary. AbstrakPedagogi Islam merupakan ilmu yang mempelajari bagaimana mendidik dan membimbing anak (peserta didik) berdasarkan nilai-nilai Islam yang bersumber dari Al-Quran dan Sunnah. Prinsip utama Pedagogi Islam adalah Tauhid (Kesatuan dengan Allah) yang diwujudkan melalui pendidikan yang mengutamakan Adab dan Ilmu untuk membentuk individu yang berakhlak mulia. Penelitian dalam artikel ilmiah ini bertujuan untuk mengeksplorasi dan menganalisis implementasi Pedagogi Islam dalam pembentukan karakter siswa di SMA Darul Hikam. Penelitian ini menggunakan pendekatan kualitatif dengan menggunakan metode studi literatur dan observasi yang dilakukan di SMA Darul Hikam. Hasil penelitian menunjukkan bahwa SMA Darul Hikam sebagai lembaga pendidikan Islam telah mengadopsi Pedagogi Islam dalam setiap aspek pendidikannya. Namun, untuk menerapkan Pedagogi Islam secara efektif, sekolah harus terus mengevaluasi dan meningkatkan kompetensi guru, khususnya dalam Pedagogi Islam. Oleh karena itu, pembinaan yang rutin dan berkala kepada setiap guru dan pendidik sangat diperlukan.